Nigeria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
This Selected Issues paper presents the current status of fiscal decentralization in Nigeria; discusses issues in reference to revenue assignment, distribution rules, and expenditure devolution; and analyzes the key challenges posed by the Nigerian model of fiscal decentralization. The paper also provides a statistical report for Nigeria on gross domestic product by sector of origin at current prices, constant 1990 prices, expenditure category at current prices, and constant 1990 prices; consolidated government revenue, finance, and expenditure; federal accounts operations; monetary survey during 1995-2000; summary of the tax system as of March 2001, and so on.